Characterization of Wet-electrospun Poly (ε-caprolactone)/Poly (L-lactic) Acid with Calcium Phosphates Coated with Chitosan for Bone Engineering - Salehi, Majid; Bastami, Farshid (Regeneration, Reconstruction & Restoration (Triple R), 2016)
Introduction: Remarkable advances have been made in the development of scaffolds with favorable characteristics for bone tissue engineering using different techniques. Recently, electrospinning process for fabrication of fibrous matrices have gained popularity, mainly because of structural similarity to the extracellular matrix. In this study, the influence of in situ formation of calcium phosphates (CP) stabled with chitosan (CT) layer on the physicochemical properties of the wet-electrospun poly (ε-caprolactone)/poly (L-lactic) acid (PCL/PLLA) scaffolds was evaluated. Materials and Methods: To prepare three-dimensional (3D) fibrous scaffold, PCL/PLLA 10% (w/v) blend was fabricated via wet-electrospinning technique. The fabricated scaffolds were characterized regarding morphology, porosity, hydrophilicity and mechanical strength using scanning electron microscopy (SEM), liquid displacement technique, contact angle measurement and mechanical tests, respectively. Moreover, cell adhesion and viability of human adipose-derived stem cells (hASCs) seeded on the scaffolds were investigated using SEM, MTT assay and DAPI staining. Results: Wet-electrospun fibers displayed random, dispersive and non-woven morphology. Porosity of the fabricated scaffolds was 80% and CT coating improved the water contact angle value. In vitro seeding of ADSCs on PCL/PLLA/CP+CT demonstrated enhanced cell proliferation and attachment compared to the PCL/PLLA blend. Porosity, wettability, mechanical properties and biocompatibility of the PCL/PLLA scaffolds have significantly influenced by both in situ formation of CP and CT coating. Conclusion: The results indicated that the PCL/PLLA scaffold spun into water/ethanol modified with NaOH (pH 10) coagulation bath with in situ surface formation of CP and CT coating can be a candidate scaffold for bone tissue engineering.